Religious Moderation of Indonesian Muslim Adolescents - Syukrilla, Wara Alfa; Nihayah, Zahrotun; Fayruz, Mohammad (Tazkiya Journal of Psychology, 2024)
In Indonesia's diverse society, tensions and conflicts among various groups of religions often disrupt social harmony. Therefore, it emerges the concept of religious moderation which is currently adopted as a national policy in Indonesia to counter intolerance and radicalism. This study aimed to identify the factors influencing religious moderation in  Indonesian Muslim adolescents. The instruments used in this study are the modified Parental Authority Questionnaire (PAQ), the Indonesian version of the Muslim Daily Religiosity Assessment Scale (MUDRAS), and the Religious Moderation Scale. The religious moderation instrument consists of three dimensions: national commitment, anti-violence, and accommodation of local culture. The confirmatory factor analysis (CFA) was employed to test construct validity. Using multiple linear regression we evaluate the effect of religiosity and parenting style on religious moderation. The sample of this study was 339 Indonesian Muslim late adolescents aged 17-22 years old from 22 provinces in Indonesia. The results showed that parenting styles and religiosity are significant predictors that positively influence religious moderation, both simultaneously and partially. The findings of this study suggest that parenting style and religiosity are the factors influencing religious moderation of Indonesian Muslim late adolescents. The findings of this study further emphasize the importance of the family's role in shaping adolescents' attitudes toward religion.